Implementasi Akad Ijarah Muntahiya Bi Al-Tamlik (IMBT) Perspektif Fatwa DSN-MUI Nomor 27 Tahun 2002 & Hukum Islam - Jamaluddin (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2020)
The Ijarah Muntahiya bi al-Tamlik (IMBT) contract is a lease agreement that ends with the transfer of property rights by means of sale and purchase (grant) at the end of the lease period. In the perspective of Islamic law, the IMBT contract is in accordance with the principles, pillars, and some terms of the contract. Unfulfilled contract conditions, namely the requirement for legal certainty. Meanwhile, in the perspective of the DSN-MUI Fatwa Number 27/2002 and Islamic Law, the IMBT agreement is an anonymous agreement that arises from the existence of the principle of freedom of contract. The IMBT contract is in accordance with the terms and elements of the agreement. IMBT legal consequences are rights and obligations. This scientific paper will examine the normative and applicable aspects of law. Legal norms that are included in the realm of unwritten law in the context of laws and regulations in Indonesia concerning Sharia Economics are DSN-MUI fatwas, especially regarding IMBT which has been perceived as a national law, (Law Number 21 of 2008, concerning Islamic Banking), Bank Regulations Indonesia (BI), the Financial Services Authority (OJK) and Sharia Financial Institutions (KLS) as an effort to apply the law in an applicative manner.